Pemberdayaan Masyarakat Berbasis Literasi: Studi Kasus Taman Baca Masyarakat Matahari Indonesia Kediri - Agustiani, Dilla Hardina; Wicaksono, M. Fikriansyah (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2021)
Taman Baca Masyarakat (TBM) is a non-formal education service that is present in the midst of society to provide benefits and positive influence for the community. This non-profit-oriented institution has a big role in the empowerment process of the surrounding community. TBM Matahari Indonesia is one of the TBM established to provide free book reading services that can be used by the Kediri community for educational purposes. TBM also seeks to improve community welfare through various literacy activities. Based on this, this study seeks to reveal the community empowerment process through literacy-based activities at TBM Matahari Indonesia Kediri. This research needs to be done to determine the roles and obstacles felt by TBM Matahari Indonesia in empowering the community through literacy. In the compilation process, this research uses a case study method with a qualitative approach. While the steps in analyzing the research data are through the analysis stage, the data presentation stage, and the conclusion stage. The results and discussion in this study is TBM Matahari Indonesia plays an important role in providing a forum for creativity and exploring the hidden talents possessed by children who live around TBM. Meanwhile, the obstacles experienced by TBM Matahari in empowering the community are limited collections, lack of human resources and the lack of funding for TBM development.